PENGARUH PENGAWASAN INTERN, SISTEM ANGGARAN BERBASIS KINERJA DAN SISTEM INFORMASI PENGELOLAAN KEUANGAN DAERAH TERHADAP KINERJA SATUAN KERJA PERANGKAT DAERAH (Studi Empiris Pada SKPD Kabupaten Rokan Hulu) - Tri Rosmarini; Ria Nelly Sari; Lila Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to examine the influence of the internal control, performance based budgeting system, financial management information system on SKPD performance. The population in this study were employed who worked in the SKPD Kabupaten Rokan Hulu (27 government agencies). The sampling method used in this study is proportioned stratified random sampling method. The respondent in this study is the employee Eselon III and Eselon IV SKPD. The sample used in this study were 108 respondents. The hypotheses then tested is multiple linear regression analysis by using SPSS version 20.0. The result of this study indicated that theinternal control, performance based budgeting system, financial management information system has significantly effect on SKPD performence. The magnitude of the effect (R2) the internal control, performance based budgeting system, financial management information system, the performance of SKPD was ,45,7%. While the remaining 54,3% is influenced by other independent variabel that are not observed in this study.Keywords : Performance, Budgeting, Financial, Information System and Internal Control.